Gender and ethnicity differences manifested in chemistry achievement and self-regulated learning - Veloo, Arsaythamby (Canadian Center of Science and Education, 2015)
The aim of this study is to examine whether gender and ethnicity differences are manifested in chemistry achievement and self-regulated learning among a matriculation programme students in Malaysia.The result of students’ midterm chemistry exam was used as the measure of chemistry achievement.The information of self-regulated learning was collected by using a survey questionnaire that was adapted from the Motivated Strategies and Learning Questionnaire (MSLQ). Random sampling method was utilized to select 358 students of Matriculation Science One-Year Programme.The results of gender differences showed that male students obtained significantly higher achievement in chemistry compared to female counterparts whereas there was no significant gender difference in self-regulated learning. The results of ethnicity differences confirmed that there was a significant difference in chemistry achievement between Malay and Chinese students, Malay and Indian students, respectively. In terms of self-regulated learning, however, a significant difference was found only between Malay and Indian students.The findings suggest that science instructors in higher education institutions utilize the MSLQ to get the information about students’ self-regulatory level and motivational level, design a “gender-based initiative” to address the lower science achievement of female students, and be ready to having learning resources and pedagogical practices available for a learning condition with diverse groups of different ethnicities.